The relationship between contributing factors and the usage of UiTM student portal / Nur Amalina Abdullah, Nur Jannatulnaim Mohd Safee and Nurul Alyaa Fatin Ariffin - Abdullah, Nur Amalina; Mohd Safee, Nur Jannatulnaim; Ariffin, Nurul Alyaa Fatin (2012)
The purpose of the study is to identify contributing factors and the usage of student portal in UiTM Dungun, Terengganu. Student Portal in UiTM is the system that allows students to access to the services provided by University. The study found there were three factors that contributing to the usage of student portal which are perceived ease of use, perceived usefulness and perceived trustworthy. The questionnaire was distributed to 200 students and it is for the data collection procedures. In addition, Pearson Correlation method used to determine the degree of correlation between the independent variables and dependent variables. Data collected from students of UiTM Dungun and involved degrees’ student from semester one to semester six. In addition, correlation method used to identify contributing factors to determine the most dominant factors that affecting to usage of student portal in UiTM. From the study, the most dominant factor contributes to the usage of student portal is perceived ease of use.